TO DEVELOP STUDENTS’ SKILLS AND ABILITIES TO USE INTELLIGENT SYSTEMS IN E-LEARNING ENVIRONMENT - M.E.Mamarajabov (Galaxy International Interdisciplinary Research Journal, 2022)
This article indicate to the aspects that are necessary for the development of students' competencies in the use of intelligent systems in the higher education system. Information is given about the current role and importance of intelligent systems, areas of application, and the advantages of intelligent systems of students'.